Performance of intercropping corn on manure oil palm plantations on dry land - Umar Harun, Muhammad; Yakup, Yakup; Seprila, Marlin; Priatna, Satria Jaya; Sopiana, Rina; Habibulloh, Habibulloh (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2025)
The intercroping area (IC) is around 0.5 ha from one hectare of mature oil palm (YH). The research aimed to observe the growth and yield of corn from the Bisi 16 variety in oil palm plantations from the SJ 5 variety and the effect of corn as IC on oil palm. The research location was in Mesuji Raya Sub-district, Ogan Komering Ilir, South Sumatra, from April 2024 to July 2024. The interspace number of oil palm of 1 ha were 12  and it was six interspaces as the object research was as frond staking. The research method used was non-experimental.  Each of front staking had two sample plots of corn (3×3 m), and samples  selected for each plot were 15 crops.  For oil palm (8×8×8 m) two samples of crops were beside the corn plot.  The total of  oil palm samples was 24 crops from oil palm IC, and compared to 24 crops from  monoculture.  The research results showed that the growth of IC corn was lower for plant height (16%), and the reduction in corn yield (26%) from one ha compared to the description. The total  yield from corn IC was approximately 2.09 tons of corn shells, which were lower from monoculture description. The growth and yield of oil palm IC were better than monoculture, with an increase a number of fruit bunches (9%) and FFB weight (11%).  Corn is an intercrop/polyculture crop in oil palm plantations after one or two years of production.